Neuropsychiatric Disturbance in Huntington’s Disease: Approach to Management - J. Jay; V. Kumar; P. Bidkhanian; E. Garrels; Y. Segal; B. Susaimanickam (European Psychiatry, 2022)
Introduction Huntington’s Disease (HD) is an autosomal dominant, neurodegenerative condition with a prevalence of 10.6-13.7 per 100,000, caused by the trinucleotide CAG (cytosine, adenine, guanine) repeat expansion in the HTT gene. HD is characterized by a range of motor, cognitive, and psychiatric symptoms, the latter of which usually manifest prior to the onset of motor or cognitive disturbances. Amongst psychiatric symptoms, changes in personality are most common, followed by depression. Psychosis has a higher prevalence in those with early-onset HD.